Effects of training of isokinetic potentials of dynamic knee stabilizers of football players - Alic, H.; Selimovic, N.; Bajramovic, I. (Sport Science - International Scientific Journal of Kinesiology, 2015)
Abilities of strong and coordinated performance are important and necessary for function of all football activities. Verhejn (1997) states that footballers need strength for everything they do. Modern football demands of a player proportional development of all muscle body areas through integration of training of strenght into one complete training. Problem of the research is determining the effect of programmed training of isokinetic potentials of dynamic stabilizers in footballers, with the goal of integrating training contents into complete sport preparation of a footballer. Sample subjects used in research are junior footballers (U-18) of quality junior league of B&H in competition; season 2010/ 2011. There were 20 subjects altogether. Criteria was: 15 played games in the last season, participation in training of at least 80% in the last season and at least 4 years of experience in playing football. Biodex Isokinetic System is used for testing strong potentials of footballers (speed 60 °/s). Initial and final testing was performed. Between tests there was programmed training process of strength of dynamic knee stabilizers (12 weeks). 36 training programmed stimulus (3 training stimulus a week) were performed in the introductory preparation part of training. Structure of programmed exercises was consisted of: squats, lunge, duels, pushing, jumps, short sprints and endurance. Functional exercises of strength were used and as they developed, they progressed into exercises for specific situations. Determining quantity differences between initial and final measurement was performed by T-test for dependent samples. Treated variables which include muscle potential of knee extensor and knee flexor: EXTLEF60 - max. torque of knee extensor of the left leg; EXTRIG60 - max. Torque of knee extensor of the right leg; EXTWLF60 - complete work of knee extensors of left leg; EXTWRG60 - complete work of knee extensors of right leg ; AVGPELF60 - average strength of knee extensor of left leg; AVGPERG60 - average strength of knee extensor of right leg; FLXLEF60 - max. Torque of knee flexor of left leg; FLXRIG60 - max. Torque of knee flexor of right leg; FLXTWLF60 - complete work of knee flexor of left leg; FXTWRG60 - complete movement of knee flexor of right leg; AVGPFLF60 - average strenght of knee flexor of left leg; AVGPFRG60 - average strenght of knee flexor of right leg. Research results have shown statistically significant differences between initial and final measurement (p<0.05) in favour of final measurement. Research shows that using exercises and movements based on your own body weight (squats, lunge, duels, sprints, jumps, pushing, endurance) which are specific for football, led by adequate distribution of physical burden and certain periods of time, improve strength performance without disturbing football performance. We need to look for reasons in adequate functional exercises, which in progress, turned into exercises for specific situations. Generally saying, it is necessary to find compatibility in exercise and situational performance and to try to accomplish multiple effects with one exercise.